Mahuldiha Days - "Agnihotri, Anita" (New Delhi, 2018)
Set deep in the forests of Bengal, India, Mahuldiha Days is the moving story of a young woman coming of age in her personal and professional life. Anita Agnihotri paints a vivid picture in this novel of life in a rural Indian setting that is quickly vanishing.
Keywords: Fiction